Evaluation of Cell Models to Study Monocyte Functions in PMM2 Congenital Disorders of Glycosylation - de Haas, Paola; de Jonge, Marien I.; Koenen, Hans J. P. M.; Joosten, Ben; Janssen, Mirian C. H.; de Boer, Lonneke; Hendriks, Wiljan J. A. J.; Lefeber, Dirk J.; Cambi, Alessandra (Frontiers in Immunology, 2022)
Congenital disorders of glycosylation (CDG) are inherited metabolic diseases characterized by mutations in enzymes involved in different steps of protein glycosylation, leading to aberrant synthesis, attachment or processing of glycans. Recently, immunological dysfunctions in several CDG types have been increasingly documented. Despite these observations, detailed studies on immune cell dysfunction in PMM2-CDG and other CDG types are still scarce. Studying PMM2-CDG patient immune cells is challenging due to limited availability of patient material, which is a result of the low incidence of the disease and the often young age of the subjects. Dedicated immune cell models, mimicking PMM2-CDG, could circumvent many of these problems and facilitate research into the mechanisms of immune dysfunction. Here we provide initial observations about the immunophenotype and the phagocytic function of primary PMM2-CDG monocytes. Furthermore, we assessed the suitability of two different glycosylation-impaired human monocyte models: tunicamycin-treated THP-1 monocytes and PMM2 knockdown THP-1 monocytes induced by shRNAs. We found no significant differences in primary monocyte subpopulations of PMM2-CDG patients as compared to healthy individuals but we did observe anomalous surface glycosylation patterns in PMM2-CDG patient monocytes as determined using fluorescent lectin binding. We also looked at the capacity of monocytes to bind and internalize fungal particles and found a slightly increased uptake of C. albicans by PMM2-CDG monocytes as compared to healthy monocytes. Tunicamycin-treated THP-1 monocytes showed a highly decreased uptake of fungal particles, accompanied by a strong decrease in glycosylation levels and a high induction of ER stress. In contrast and despite a drastic reduction of the PMM2 enzyme activity, PMM2 knockdown THP-1 monocytes showed no changes in global surface glycosylation levels, levels of fungal particle uptake similar to control monocytes, and no ER stress induction. Collectively, these initial observations suggest that the absence of ER stress in PMM2 knockdown THP-1 cells make this model superior over tunicamycin-treated THP-1 cells and more comparable to primary PMM2-CDG monocytes. Further development and exploitation of CDG monocyte models will be essential for future in-depth studies to ultimately unravel the mechanisms of immune dysfunction in CDG.